MENITI ULANG MASALAH ETIKA DAN NETRALITAS ASN DI ERA REFORMASI BIROKRASI - Khaidar Azmi (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2023)
Bureaucratic reform is a big job that requires large resources, earnest efforts and strong commitment from all levels of government management. Bureaucratic reform must be able to mobilize the full potential of the Indonesian nation, first of all we should clean up bureaucratic diseases, and if it is not immediately resolved it can cause the government not going well, because it reduces trust in the community. Therefore, the Government of Indonesia is currently carrying out bureaucratic reforms that must make corrections and retrace the ethics of the bureaucracy or public administration. Bureaucratic ethics related to the mentality and morality of the bureaucratic apparatus in carrying out government functions, because many cases of ASN in Indonesia involve problems related to bureaucratic ethics, the most common in Indonesia is corruption. Many cases of corruption prove that Indonesia's bureaucratic ethics is still weak and requires improvement in bureaucratic ethics. Apart from that, in government it is also known as administrative or bureaucratic neutrality. The neutrality of the bureaucracy is not a new thing, but with state administration as an organ of the bureaucracy in Indonesia it will definitely be neutral. According to Sondang P, the bureaucracy must be neutral, meaning that this principle is interpreted by saying that the government bureaucracy must continue to function properly, regardless of the influence of the prevailing political parties.